2012
DOI: 10.1038/bjc.2012.93
|View full text |Cite
|
Sign up to set email alerts
|

Serum matrix metalloproteinase 9 and colorectal neoplasia: a community-based evaluation of a potential diagnostic test

Abstract: Background:A blood test may be a more acceptable routine colorectal cancer (CRC) screening test than faecal occult blood test, flexible sigmoidoscopy or colonoscopy, and could be safer and cheaper. We evaluated the accuracy of a serum matrix metalloproteinase (MMP9) test for CRC in a non-presenting symptomatic population.Methods:A cohort, aged 50–69 with lower gastrointestinal symptoms, was identified by community-based survey. Accuracy of serum MMP9 was assessed by comparison with colonoscopy. Logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
0
31
3
2
Order By: Relevance
“…However, in another study including 63 CRC, 27 AA and 46 HC, 32 higher levels were found in neoplastic lesion samples, with no difference between CRC and AA. In a third study, 14 35 adenomas, 75 CRC and 70 HC were included. In this case, MMP levels were higher in CRC compared with adenomas or HC and in adenomas compared with HC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in another study including 63 CRC, 27 AA and 46 HC, 32 higher levels were found in neoplastic lesion samples, with no difference between CRC and AA. In a third study, 14 35 adenomas, 75 CRC and 70 HC were included. In this case, MMP levels were higher in CRC compared with adenomas or HC and in adenomas compared with HC.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 This is particularly interesting since the major goal of screening is the detection of advanced colorectal neoplasms, including not only CRC but also AA. 25 Small NAA present low risk of transformation into CRC and are not considered an issue in CRC screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sie weisen im Serum Genommutationen oder die entsprechend veränderten Proteinprodukte nach. Der Test zum Nachweis von Serum-Matrix-Metalloproteinase (MMP9) konnte immerhin bereits eine Sensitivität von 79 % und eine Spezifität von 70 % erreichen [35]. Ein anderer Test zum Nachweis hypermethylierter DNA des Septin-9-Gens im Serum weist eine Sensitivität von 63-72 % und eine Spezifität von 89-90 % auf [11,20].…”
Section: Stuhltests ▼unclassified
“…In a very recent study, Wilson et al [24] evaluated the accuracy of MMP-9 for CRC in an asymptomatic population. From 748 patients overall, 46 cases of CRC were identified.…”
Section: Tissue Inhibitor Of Metalloproteinase Type 1 (Timp-1)mentioning
confidence: 99%